2015
DOI: 10.1186/s12889-015-1476-0
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions and explanatory models of viral hepatitis B & C among immigrants and refugees: a narrative systematic review

Abstract: BackgroundHepatitis B and C (HBV, HCV) infections are associated with high morbidity and mortality. Many countries with traditionally low prevalence (such as UK) are now planning interventions (screening, vaccination, and treatment) of high-risk immigrants from countries with high prevalence. This review aimed to synthesise the evidence on immigrants’ knowledge of HBV and HCV that might influence the uptake of clinical interventions. The review was also used to inform the design and successful delivery of a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 83 publications
0
65
0
3
Order By: Relevance
“…Studies of patients with liver disease worldwide have suggested that patients' explanations of symptoms (such as fatigue and tiredness) may be influenced by folk health beliefs, which affect the health behaviours and management of the disease, including adopting new lifestyles or alternative/traditional treatments (Brener et al, 2016 (Fang & Stewart, 2018), remedial or healing herbs (Fang & Stewart, 2018;Giles-Vernick et al, 2016). In the patients' experience, these treatments are often used as alternative treatments instead of usual medical treatment (Fang & Stewart, 2018;Lee et al, 2017;Owiti et al, 2015). To date, conventional medical treatments for chronic hepatitis B include active adherence to antiviral medications and follow-up enhanced by developing a self-management programme (Kong et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of patients with liver disease worldwide have suggested that patients' explanations of symptoms (such as fatigue and tiredness) may be influenced by folk health beliefs, which affect the health behaviours and management of the disease, including adopting new lifestyles or alternative/traditional treatments (Brener et al, 2016 (Fang & Stewart, 2018), remedial or healing herbs (Fang & Stewart, 2018;Giles-Vernick et al, 2016). In the patients' experience, these treatments are often used as alternative treatments instead of usual medical treatment (Fang & Stewart, 2018;Lee et al, 2017;Owiti et al, 2015). To date, conventional medical treatments for chronic hepatitis B include active adherence to antiviral medications and follow-up enhanced by developing a self-management programme (Kong et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Studies of patients with liver disease worldwide have suggested that patients’ explanations of symptoms (such as fatigue and tiredness) may be influenced by folk health beliefs, which affect the health behaviours and management of the disease, including adopting new lifestyles or alternative/traditional treatments (Brener et al, ; Burnham et al, ; Owiti, Greenhalgh, Sweeney, Foster, & Bhui, ). Traditional treatments are often related to cultural beliefs, including spiritual healing (Fang & Stewart, ), remedial or healing herbs (Fang & Stewart, ; Giles‐Vernick et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the prevalence of chronic HCV in the United Kingdom among South Asians, and especially among migrants from Pakistan, may be as high as 2.7%, which is over fivefold higher than in the general population (0.5%)[64]. In Italy, the prevalence of HCV among Sub-Saharan refugees varied between 2.7% and 7.1%, while in Spain it was 12.5%, considerably higher than in the autochthonous population[65].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of genotype 4 among high-risk individuals in France increased from 15% of infections in 2003 to 22% in 2012. These changes in the trends of genotypes in these countries corresponds well with the increasing numbers of migrants from Africa[64]. As the foreign-born populations expand, the integration dynamics of HCV will become globally imminent[67].…”
Section: Resultsmentioning
confidence: 99%